Optimizing Foundation Asset Status Through Assistance with Land Registration for the "M" Mosque in Malang City - Yaris Adhial Fajrin; Nu'man Aunuh; Radhityas Kharisma Nuryasinta (Jurnal Dedikasi Hukum, 2023)
Law number 41 of 2004 concerning Waqf explains that the management and development of waqf land can be carried out by Nazhir in the form of a legal entity. However, there are still many mosques managed by the Foundation that still stand on non-waqf land or in this case the land status does not yet have legal documents such as certificates. This problem is also experienced by the "M" Mosque, one of the mosques in the city of Malang which has been established since 1983. This service program aims to provide assistance and legal knowledge to Foundation administrators regarding the legality registration of land assets regarding mosque management. This service uses the PAR (Participatory Action Research) method, where the stages include planning, implementation and evaluation activities. This legal assistance activity was carried out in January - July 2023. The results of the service showed that the reason the mosque was still standing on non-waqf land was the lack of knowledge of the Foundation management regarding land legality registration procedures. Appropriate assistance to be provided is in the form of counseling and processing legal documents in registering waqf certificates. This service activity through mentoring is carried out as a method of providing information about strategic steps in managing the Foundation's assets so that they are more optimal.   Abstract Optimalisasi Status Aset Yayasan Melalui Pendampingan Pendaftaran Tanah Masjid “M” Kota Malang. Undang-Undang No. 41 Tahun 2004 tentang Wakaf menjelaskan bahwa pengelolaan dan pengembangan tanah wakaf dapat dilakukan oleh Nazhir yang berbentuk badan hukum. Akan tetapi masih banyak masjid yang dikelola Yayasan masih berdiri di atas tanah non wakaf atau dalam hal ini status tanah belum memiliki dokumen legal seperti sertifikat. Persoalan ini yang juga dialami Masjid “M”, salah satu masjid di kota Malang yang telah berdiri sejak tahun 1983. Program pengabdian ini bertujuan untuk memberikan pendampingan dan pengetahuan hukum kepada pengurus Yayasan tentang pendaftaran legalitas aset tanah terhadap pengelolaan masjid. Pengabdian ini menggunakan metode PAR (Participatory Action Research), dimana tahapannya meliputi kegiatan perencanaan, pelaksanaan, dan evaluasi. Kegiatan pendampingan hukum ini dilaksanakan pada bulan Januari – Juli 2023. Hasil pengabdian diperoleh penyebab masjid masih berdiri di atas tanah non wakaf yaitu kurangnya pengetahuan pengurus Yayasan mengenai prosedur pendaftaran legalitas tanah. Pendampingan yang sesuai untuk diberikan yaitu dalam bentuk penyuluhan dan pengurusan dokumen-dokumen hukum dalam pendaftaran sertfikat wakaf. Kegiatan pengabdian melalui pendampingan ini dilakukan sebagai metode pemberian informasi tentang langkah strategis pengelolaan aset Yayasan agar lebih optimal.